Mastering Powerpoint 2000 - Murray, Katherine (San Francisco : Sybex, 2002)
Urban disturbances, concerns about the fate of asylum seekers and renewed debates about the nature of ethnic identity and citizenship have all combined to give ethnic differences a high public and policy profile. This book explores the diverse experiences of ethnic disadvantage and challenges common assumptions.
Includes index.
Keywords: Presentation graphics software; Microsoft PowerPoint (Computer file).